Association of Outdoor Artificial Light at Night With Mental Disorders and Sleep Patterns Among US Adolescents - Paksarian, Diana; Rudolph, Kara E; Stapp, Emma K; Dunster, Gideon P; He, Jianping; Mennitt, Daniel; Hattar, Samer; Casey, Joan A; James, Peter; Merikangas, Kathleen R (JAMA psychiatry (Chicago, Ill.), 2020)
Indoor nighttime light exposure influences sleep and circadian rhythms and is known to affect mood-associated brain circuits in animals. However, little is known about the association between levels of nighttime outdoor light and sleep and mental health in the population, especially among adolescents. To estimate associations of outdoor artificial light at night (ALAN) with sleep patterns and past-year mental disorder among US adolescents. This population-based, cross-sectional study of US adolescents used the National Comorbidity Survey-Adolescent Supplement, a nationally representative cross-sectional survey conducted from February 2001 through January 2004. A probability sample of adolescents aged 13 to 18 years was included. Analyses were conducted between February 2019 and April 2020. Levels of outdoor ALAN, measured by satellite, with means calculated within census block groups. ALAN values were transformed into units of radiance (nW/cm2/sr). Self-reported habitual sleep patterns (weeknight bedtime, weeknight sleep duration, weekend bedtime delay, and weekend oversleep) and past-year mood, anxiety, behavior, and substance use disorders, measured via an in-person structured diagnostic interview. Parent-reported information was included in behavior disorder diagnoses. Among 10 123 adolescents (4953 boys [51.3%]; mean [SE] age, 15.2 [0.06] years [weighted]; 6483 for behavior disorder outcomes), ALAN was positively associated with indicators of social disadvantage, such as racial/ethnic minority status (median [IQR] ALAN: white adolescents, 12.96 [30.51] nW/cm2/sr; Hispanic adolescents: 38.54 [47.84] nW/cm2/sr; non-Hispanic black adolescents: 37.39 [51.88] nW/cm2/sr; adolescents of other races/ethnicities: 30.94 [49.93] nW/cm2/sr; P < .001) and lower family income (median [IQR] ALAN by family income-to-poverty ratio ≤1.5: 26.76 [52.48] nW/cm2/sr; >6: 21.46 [34.38] nW/cm2/sr; P = .005). After adjustment for several sociodemographic characteristics, as well as area-level population density and socioeconomic status, this study found that higher ALAN levels were associated with later weeknight bedtime, and those in the lowest quartile of ALAN reported the longest weeknight sleep duration. Those in the highest quartile of ALAN went to bed 29 (95% CI, 15-43) minutes later and reported 11 (95% CI, 19-2) fewer minutes of sleep than those in the lowest quartile. ALAN was also positively associated with prevalence of past-year mood and anxiety disorder: each median absolute deviation increase in ALAN was associated with 1.07 (95% CI, 1.00-1.14) times the odds of mood disorder and 1.10 (95% CI, 1.05-1.16) times the odds of anxiety disorder. Further analyses revealed associations with bipolar disorder (odds ratio [OR], 1.19 [95% CI, 1.05-1.35]), specific phobias (OR, 1.18 [95% CI, 1.11-1.26]), and major depressive disorder or dysthymia (OR, 1.07 [95% CI, 1.00-1.15]). Among adolescent girls, differences in weeknight bedtime by ALAN (third and fourth quartiles vs first quartile) were greater with increasing years since menarche (F3, 8.15; P < .001). In this study, area-level outdoor ALAN was associated with less favorable sleep patterns and mood and anxiety disorder in adolescents. Future studies should elucidate whether interventions to reduce exposure to ALAN may positively affect mental and sleep health.